An Investigation of Obstacles Experienced by 8th Grade Junior High School Student in Speaking Performance at SMP Swasta Muhammadiyah 1 Medan - Maharani Amelia Hasibuan; Ariatna (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study investigated the obstacles faced by 8th grade students at SMP Swasta Muhammadiyah 1 Medan in speaking performance and the reasons behind these obstacles. Using Ur's (1996) theory, qualitative methods like observation and interviews were employed. The analysis revealed three main problems: inhibition, nothing to say, and mother tongue use. Inhibition was the primary issue, involving verbal disfluency, facial expressions, voice characteristics, and physical behavior. Nothing to say led to superficial content, while mother tongue use, such as code-switching, was a minor obstacle. Several causes of those obstacles, including affective factors such as anxiety, worries, nervousness, shyness, forgetfulness, confusion, lack of confidence, and discomfort; linguistic factors, such as the fear of making mistakes in pronunciation, grammar, and word choice, unfamiliarity with speaking in English, difficulty in organizing words or sentences, and limited proficiency in English; meanwhile performance conditions involve issues such as time pressure, lack of preparation and external disturbances from peers.